RESISTENSI OBAT ANTI TUBERKULOSIS TERHADAP PASIEN TUBERKULOSIS PARU DENGAN KOMORBID - Ratu, Aisyah Ramadhani Paduan; Shalshabil , Monique; Amalia , Shaeny Putri (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Nearly a quarter of people worldwide have been infected with TB. However, in the process of controlling and preventing tuberculosis, there is a new challenge of OAT resistance in tuberculosis patients. This resistance occurs in both treated and newly diagnosed patients. This condition is largely caused by sufferers' inconsistent habits during their treatment. Thus, further explanation is needed regarding the components that influence OAT resistance. This research is a literature review, based on articles from Google Scholar, Science Direct, and Pub Med. The variables examined in this literature review are treatment history, treatment compliance, contact history, and comorbid history. The search results obtained a total of 14,131 articles, of which only 9 articles were suitable. Most studies reveal that treatment history, adherence to treatment, and previous history of contact with TB patients have a significant relationship with the incidence of OAT resistance in TB patients. Meanwhile, DM history is a variable that can also indirectly influence the occurrence of OAT resistance. To obtain significant and more valid research results, further research is needed to analyze the clinical factors that have the most dominant influence on the occurrence of drug resistance in TB patients..